009 The effect of cardiac magnetic resonance on human circulating leukocytes. (3rd April 2017) - Critchley, William; Reid, Anna; Stone, John; Ball, Alexandra; Major, Triin; Clark, David; Waldron, Nick; Fortune, Christien; Lagan, Jakub; Lewis, Gavin; Naish, Josephine; Schelbert, Erik; et al.
Abstract : Aims: Investigators have proposed that cardiovascular magnetic resonance (CMR) should have restrictions similar to those of ionising imaging techniques due to proposed alterations to leukocytes. We aimed to investigate the acute effect of CMR on leukocyte DNA integrity and cell viability in vitro, and in a large cohort of patients in vivo . Methods and results: In vitro study: Peripheral blood mononuclear cells (PBMC) were isolated from healthy volunteers and assessed: 1) immediately following PBMC isolation, 2) after standing on the benchside as a temperature and time control, 3) after a standard CMR scan. Histone H2AX phosphorylation (γ-H2AX), an indicator of DNA damage, and leukocyte counts were quantified using flow cytometry. In vivo study: Blood samples were taken from 64 consecutive consenting patients immediately before and after a standard clinical scan. Samples were analysed for T cell count and γ-H2AX expression. CMR scanning was associated with a significant increase in leukocyte γ-H2AX expression, indicating DNA damage occurs. We also observed a trend towards a significant decrease in absolute leukocyte numbers in vitro following CMR. CMR was not associated with a significant change in γ-H2AX expression in vivo, although there were significant inter-patient variations. There was a significant reduction in circulating T cells following CMR. Conclusion: CMR was not associated with DNA damage in vivo . γ-H2AX expression varied markedly between individuals, therefore small studies using γ-H2AX as a marker of DNA damage should be interpreted with caution. CMR was associated with a statistically significant reduction in viable leukocytes, although the clinical relevance of the magnitude is unclear. Further work is warranted to contextualise these findings and delineate their impact.